The incidence, pattern and management of sexual assault in a tertiary hospital in North-western Nigeria - Shehu, Constance E.; Ekele, Ojogbane I.; Panti, Abubakar A.; Ango, Ibrahim; Ekele, Bissallah A.; Umar, Mohammed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Sexual assault is any sexual act performed by one person on another without the person’s consent or on a victim who is incapable of giving consent. It is a violation of basic human rights, a gender-based issue and a violent crime against both the individual and the society. The objectives of the study were to determine the incidence, pattern and management of sexual assault in Usmanu Danfodiyo University Teaching Hospital, Sokoto, Nigeria. Methods: This was a 10 - year retrospective study. Case records of sexual assault from 1st January, 2007 to 31st December, 2016 were retrieved and relevant data extracted and analyzed using the SPSS for windows version 20.0 Results: The incidence of sexual assault was 0.8%. Majority, 88 (85.4%) occurred in children and adolescents. Peno-vaginal penetration was the most common form of assault 65 (63.1%) and the assailants were known to the victims in 74 (71.9%) of the cases. Involvement of psychiatrists/psychologists in the management of the victims was poor as psychiatrists were involved in only 13 (12.6%) of the cases. Most of the victims were lost to follow up. Conclusions: Sexual assaults occurred mostly in children and adolescents in this study. Increased public awareness and preventive interventions are required especially among the at-risk age groups to enhance their safety. Training of relevant persons in the institution to offer counselling to the victims is recommended as referral for psychiatrists’ consultation was poor. It is important to institute a good tracking system to follow up the victims as most are lost to follow up.